Comparing Autoimmune Hypothyroidism Patients with Normal Subjects in Terms of Serum Vitamin D - Alireza Mehdizadeh (Journal of Global Pharma Technology, 2017)
Introduction Autoimmune diseases of the thyroid known as Graves and Hashimoto are the most common autoimmune diseases that vitamin D levels of these patients is different from that of healthy individuals. In this study, we examine vitamin D level in patients with Hashimoto's thyroiditis and compare them with the healthy group. Method This research is a case-control study. In this study, 65 patients with Hashimoto thyroiditis and 60 healthy people were randomly selected. Hashimoto thyroiditis patients diagnosed recently and not treated with any hormone were referred to laboratory to examine the 25-hydroxy-vitamin D and the results were analyzed using SPSS16.Results The results of this study showed that there is no significant difference between two groups of study and control in terms of variables such as age, height, weight, 25-hydroxy D3, BMI and TSH, and gender.Discussion and conclusion there is no correlation between 25-hydroxy D3 and TSH and Anti TPO, and most of other studies confirm this result.Keywords: Autoimmune, Vitamin D, Patients.